The Matching Concept. - Berg, W. G.; Griffin, C. H.; Kircher, Paul; Mitchell, W. S.; Schrader, W. J.; Henke, Emerson (The Accounting Review, 1965)
Abstract This article discusses the matching concept in accounting as defined by the 1964 Concepts and Standards Research Study Committee of the American Accounting Association. The committee first considered whether the matching convention is still a useful concept to guide financial reporting practices. Since the fundamental long-term objective of a business entity is to earn a profit, this financial data, to be most meaningful, should include information about profit determinants, including costs and revenues. Only by including these data can the reasons for and the extent of progress of the entity toward its primary objective be disclosed. Following this thought a bit further, one's judgment regarding the effectiveness of a specific effort is improved if it can be related to its contribution toward the recognized objective of the entity. In business operations, costs, defined as resources given up or economic sacrifices made are incurred with the anticipation that they will produce revenue in excess of the outlay. Within this frame of reference, one can then say that costs constitute one measure of business effort, and revenues represent accomplishments coming from those efforts.